Musykilat al-Mu‘allim wa Hilluha fi at-Ta’lim al-Lughah al-‘Arabiyyah ‘Abra al-Intirnit Khilal Jaihah Covid-19 - Indaha Nur Wahyuni; Ali Mudlofir (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
At the beginning of 2020, the world was surprised by the outbreak of Corona Virus Disease 2019 or usually shortened as COVID-19. The World Health Organization (WHO) has proven this outbreak as a pandemic as it spreads rapidly to all countries of the world. In the education sector, the pandemic is affecting the temporary closure of schools and changing the teaching method from face-to-face to online teaching. This change causes some new problems that the teacher has not addressed in previous times. This research discusses about the teacher's problems in teaching Arabic online during the Covid-19 pandemic for the seventh grade of Nahdlatul Ulama Middle School Sidoarjo, and his objectives: (1) to learn how to teach Arabic during the Covid-19 pandemic at Nahdlatul Ulama Middle School Sidoarjo; (2) to learn about the teacher's problems in teaching Arabic online during the Covid-19 pandemic; and (3) to find out how to solve those problems. The research method used is descriptive and the data were collected in an observation, interview and documentation. The result of the research is the emergence of five new problems that have been classified into three sections according to the teacher's basic abilities: (1) the teacher's problem in planning and preparing the process of teaching Arabic online; (2) the teacher's problem in implementing and managing the process of teaching Arabic online; and (3) the teacher's problem in evaluating the results of students' online learning. The teacher collaborates with parents and school principals to solve those problems.